2005
DOI: 10.1002/dvdy.20432
|View full text |Cite
|
Sign up to set email alerts
|

RBMX gene is essential for brain development in zebrafish

Abstract: The human RBMX gene was discovered recently through its homology to the spermatogenesis candidate gene RBMY. Its position on the human X chromosome suggests that it may be involved in X-linked mental retardation syndromes. However, to date there is scant information on the in vivo role of RBMX. To address this issue, we have isolated a zebrafish rbmx orthologue and characterized its embryonic expression pattern. Zebrafish rbmx is maternally expressed and then widely expressed in the embryo up to 24 hr postfert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
6
33
0
Order By: Relevance
“…The human hnRNP-G gene is located on the X chromosome at Xq26 where several X-linked mental retardation (XLMR) syndromes have also been mapped to (Delbridge et al, 1999), suggesting a possible involvement of hnRNP-G in these mental disorders. In zebrafish, knockdown experiment of hnRNP-G by antisense morpholino indicated that hnRNP-G is required for normal embryonic development (Tsend-Ayush et al, 2005). Although current studies on the hnRNP-G protein subfamily have been focused on their function of pre-mRNA binding and splicing, other hnRNPs have already been identified as ssDNA/dsDNA-binding proteins.…”
Section: ) (B) Western Blots Were Performed To Verify the Overexprmentioning
confidence: 99%
“…The human hnRNP-G gene is located on the X chromosome at Xq26 where several X-linked mental retardation (XLMR) syndromes have also been mapped to (Delbridge et al, 1999), suggesting a possible involvement of hnRNP-G in these mental disorders. In zebrafish, knockdown experiment of hnRNP-G by antisense morpholino indicated that hnRNP-G is required for normal embryonic development (Tsend-Ayush et al, 2005). Although current studies on the hnRNP-G protein subfamily have been focused on their function of pre-mRNA binding and splicing, other hnRNPs have already been identified as ssDNA/dsDNA-binding proteins.…”
Section: ) (B) Western Blots Were Performed To Verify the Overexprmentioning
confidence: 99%
“…Even testis-specific genes that are conserved on the Y and contribute to male sex determination and fertility have widely expressed paralogues on the X from which they obviously diverged. For instance, the testis-specific spermatogenesis gene RBMY diverged from a ubiquitously expressed RBMX that may have functions in brain development (Delbridge et al 1999, Tsend-Ayush et al 2005, and TSPY (the putative gonadoblastoma gene) diverged from a widely expressed cell cycle gene TSPX (Delbridge et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, our attempts to clone its homologue from the tammar wallaby and the dunnart revealed a homologue on the marsupial X chromosome, and we soon found that the human X, too, contained a copy of this RBMX gene. This gene, expressed in brain and germ cells, is highly conserved throughout vertebrates and critical for brain development in zebrafish (Tsend-Ayush et al 2005). It is clearly the ancestor of RBMY.…”
Section: Kangaroos and Y Chromosome Degradationmentioning
confidence: 99%